Efektifitas Penggunaan Media Audiovisual pada Pembelajaran Anatomi Tubuh Manusia di Tingkat Sekolah - Gea, Sehati; Gulo, Piderman; Lase, Natalia Kristiani (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research examines the effectiveness of using audiovisual media in teaching human anatomy at school level. The literature review was carried out by analyzing various trusted sources, such as scientific journals, books and online articles. The research results showed that the application of audiovisual media was proven to increase students' understanding and learning achievement in human anatomy subjects. The most effective audiovisual media are animated videos, 3D anatomical images, and interactive simulations. Appropriate use of audiovisual media helps students understand the structure and function of the human body better. Conclusion: Audiovisual media is an effective learning strategy to improve students' understanding and learning achievement in human anatomy subjects. Teachers need to use appropriate and varied audiovisual media in learning human anatomy to achieve optimal learning outcomes